Comparing the Structural Standards of Nursing Homes in Markazi Province, Iran With International Standards - Masoud Khodaveisi; Ali Faal Araghi Nejad; Afsar Omidi; Ali Esmaili Vardanjani; Leili Tapak (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives In the recent years, the elderly pollution has increased; therefore, the availability of centers that meet their physical and emotional needs has become extremely important. Standardization is one of the approaches to improve the quality of these centers. The purpose of this study was to compare the status of structural standards in nursing homes with international standards. Methods & Materials In this descriptive, cross-sectional study, three nursing homes in Markazi Province were studied in 2017. To investigate the status of structural standards, a researcher-made checklist was used, which consisted of the staff standards, physical environment standards, and equipment standards. The validity of this checklist was confirmed using expert panel and its reliability was confirmed by parallel forms reliability. The collected data were analyzed by SPSS 23. Results Overall, the centers were in moderate situation in terms of structural standards with average score of 83.29% (mean: 674 [out of 810]). The scores of Imam Javad Nursing home, Ebrahimabad Nursing home, and Meisam Nursing home were 88.40%, 88.64%, and 72.84% (mean: 716, 718, and 590), respectively. Conclusion Considering that the structural condition of nursing homes in Markazi Province is lower than international standards, nursing home officials are recommended to improve the quality of their centers to achieve the levels of international standards, especially structural standards.